IDENTIFICATION OF ELECTROMAGNETIC ULTRA LOW FREQUENCY (ULF) SIGNAL ANOMALIES AS PRECURSORS OF A MAGNITUDE 5 EARTHQUAKE IN THE SULAWESI REGION - Anggraini, Delfira; Sirait, Ratni; Lubis, Lailatul Husna; Sibuea, Christofel Haposan Great (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Sulawesi is situated at the intersection of three tectonic plates the Indo-Australian, Eurasian, and Philippine plates. The Palu Koro fault is one of the primary causes of seismic activity in the Sulawesi region, making it vulnerable to earthquakes on this Island. As an initial step in disaster mitigation, the information provided is useful in determining the initial signs before the occurrence of an earthquake, it is necessary to identify Ultra Low Frequency (ULF) Signal Anomalies as earthquake precursors. The methods employed are those of power spectrum density (PSD) and single-station transfer function (SSTF). The analysis of anomalies suspected of being precursors to 5 earthquake events revealed that in the February 27, 2023 earthquake, the anomaly appeared twice with a lead time of 17 days. In the February 28, 2023 earthquake, the anomaly appeared twice. In the March 7, 2023 earthquake, the anomaly appeared 3 times with a lead time of 20 days. The March 28, 2023 earthquake had 6 anomalies with a lead time of 24 days. The April 6, 2023 earthquake had 5 anomalies with a lead time of 29 days. anomalies were detected with lead times ranging from 17 to 30 days. The anomaly source azimuth direction was also determined.